Perlindungan Hukum Pada Pasien Akibat Kesalahan Pemberian Obat Yang Tidak Sesuai Dengan Resep Dokter - Makahity, Yandri Julian; Narwadan, Theresia Nolda Agnes; Pariela, Marselo Valentino Giovani (PATTIMURA Law Study Review, 2025)
The Legal protection for patients as consumers in health services is not only regulated in the Health of Law, but also in Law Nomor 8 of 1999 concerning Consumer Protection which provides assurance on the safety and security of patients in consuming products. One of the examples that the author analyzes is an error in administering medication by puskesmas bandar lampung. The research objectives were to identify and analyze patient protection against pharmacists, who made mistakes in administering drugs based on a doctor's prescription and to identify and analyze the efforts patient could take in administering medication errors. The approximation method that used in this research is normative juridical research, because it examines and studies case examples. The research specification used descriptive analytical, namely legal research that is descriptive and aims to obtain a complete description (description) of the prevailing legal conditions. This study uses the legal materials needed in this study. The author use library research and scientific journals.The data collection process in this study was carried out in two stages. The first stage is through document studies in order to find information data related to legal foundations, consumer protection, pharmacy through library materials such as books, scientific papers, and the second stage through internet sites related to the object of research. The analytical method used in this research is qualitative juridical, namely research based on one law which must not conflict with other laws in order to create legal certainty in society and the data obtained is compiled qualitatively.